Death at Work Existential and Psychosocial Perspectives on End-of-Life Care - Moen, Kjetil (Studies in the Psychosocial,, 2018)
'Kjetil Moen has written a book of depth, insight and significance. It is thrill to read. He writes of a world of paradoxes and contradictions, continual absurd realities and great sadness. Here is a book for a world-wide audience that is looking for direction as the human family experiences more aging.' - Thomas M. Skovholt, Professor and Psychologist, University of Minnesota, USA; and author of The Resilient Practitioner 'A powerful, searing yet encouraging book. Vivid case studies bring to life the dilemmas and decision moments in which end-of-life professionals live... Moen combines methodological clarity, detail and philosophic reflection: it concerns us all.' - Tom Wengraf, previously Middlesex University and Birkbeck Institute of Social Research, UK; and author of Qualitative Research Interviewing This important book shines a long-overdue spotlight on the call for a reflective space and self-knowledge of the professional working in end-of-life care... and makes an empirically and clinically sound call for re-humanization of the way we relate to the dying person. - Gry Stålsett, PhD, Specialist Psychologist at Modum Bad Clinic in Vikersund, Norway This book explores how, in encounters with the terminally ill and dying, there is something existentially at stake for the professional, not only the patient. It connects the professional and personal lives of the interviewees, a range of professionals working in palliative and intensive care. Kjetil Moen discusses how the inner and outer worlds, the psychic and the social, and the existential and the cultural, all inform professionals' experience of work at the boundary between life and death. Death at Work is written for an academic audience, but is accessible to and offers insights for practitioners in a variety of fields.